European perspective on human polyomavirus infection, replication and disease in solid organ transplantation. (September 2014) - Hirsch, H. H.; Babel, N.; Comoli, P.; Friman, V.; Ginevri, F.; Jardine, A.; Lautenschlager, I.; Legendre, C.; Midtvedt, K.; Muñoz, P.; Randhawa, P.; Rinaldo, C. H.; et al.
Abstract: Human polyomaviruses (HPyVs) are a growing challenge in immunocompromised patients in view of the increasing number of now 12 HPyV species and their diverse disease potential. Currently, histological evidence of disease is available for BKPyV causing nephropathy and haemorrhagic cystitis, JCPyV causing progressive multifocal leukoencephalopathy and occasionally nephropathy, MCPyV causing Merkel cell carcinoma and TSPyV causing trichodysplasia spinulosa, the last two being proliferative skin diseases. Here, the current role of HPyV in solid organ transplantation (SOT) was reviewed and recommendations regarding screening, monitoring and intervention were made. Pre‐transplant screening of SOT donor or recipient for serostatus or active replication is currently not recommended for any HPyV. Post‐transplant, however, regular clinical search for skin lesions, including those associated with MCPyV or TSPyV, is recommended in all SOT recipients. Also, regular screening for BKPyV replication (e.g. by plasma viral load) is recommended in kidney transplant recipients. For SOT patients with probable or proven HPyV disease, reducing immunosuppression should be considered to permit regaining of immune control. Antivirals would be desirable for treating proven HPyV disease, but are solely considered as adjunct local treatment of trichodysplasia spinulosa, whereas surgical resection and chemotherapy are key in Merkel cell carcinoma. Overall, the quality of the clinical evidence and the strength of most recommendations are presently limited, but are expected to improve in the coming years.